Intenzivna rehabilitacija osemletnega otroka po popolni amputaciji in replantaciji roke nad komolcem - Bajuk, Slavica (Rehabilitacija (Ljubljana), 2008)
Background: The paper presents the rehabilitation of an 8-year-old left-handed boy after replantation of the left arm, which was amputated above the elbow by heavy workshop machinery. Methods: An intensive dynamic rehabilitation program for pain, edema, and function was performed and extended to 14 months based on continued improvement. Circumferential, range of motion (ROM), and muscle strength measurements of both upper extremities were taken to assess functionality of the replanted extremity. Results: At the beginning, the replanted arm was plegic and afunctional with edema, disturbed sensibility and no active motion distal to the injury. Passive ROM in the elbow was painful, flexion was 20°/25°, position of the forearm was 15°/50° in pronation. At the end of therapy there was no pain, no edema; scar tissue was softened; passive elbow range of motion (ROM) flexion 10°-115°, pronation 70°, supination 20°; active elbow and wrist flexion and extension, finger flexion, thumb flexion and opposition; sensibility was normal except in the ulnar nerve innervation region. Conclusions: Functionality of the replanted upper extremity improved substantially during the 14 months of intensive therapy and was still improving. Strength has increased in the inervated muscle groups. Hand grip has been improving in strength and precision, and the extremity is spontaneously used in various daily activities.
Keywords: amputacija; poškodbe; roka; replantacija; vocational rehabilitation; rehabilitacija